Investment and Consumption: Economic Policy Options in Mid-2020 - Michael Hüther (Wirtschaftsdienst)
Abstract The historically unprecedented slump in overall economic output due to the coronavirus crisis creates an urgency for economic policy responses. Demandside measures must be timely, targeted, and temporary. Addressing policy objectives beyond the economic recovery should not be the focus right now. A package of measures ranging from tax cuts to direct payments is appropriate.